A comparative study on the some haematological parameters of sakız, karayaka and crossbred of sakız x karayaka ci sheep - Şevket Arıkan; Arzu Yiğit; Halil Akçapınar; Nurgül Zengin; Umut Taşdemir (Eurasian Journal of Veterinary Sciences)
This study was conducted to compare the haematological parameters of Sakız male and Karayaka female with crossbred of Sakız X Karayaka male and female sheep. In the present study, 38 healthy sheep (7 male Sakız, 9 female Karayaka, and 15 female and 7 male crossbred sheep) were used. Blood samples obtained from the animals were analysed for erythrocyte (RBC) and leucocyte (WBC) numbers, haemoglobin concentrations (Hb). haematocnt values (PCV), sedimentation rates and percentages ot lymphocytes, neutrophyls, monocytes, eosinophyls and ba-sophyls. Mean corpuscular volume (MCV), mean corpuscular haemoglobin (MCH) and mean corpuscular haemoglobin concentration (MCHC) were also calculated. As a result, in order to establishing normal haematological values of Sakız, Karayaka and crossbred of Sakız X Karayaka sheep, present results also indicate that some of blood parameters of crossbred sheep were dilferenl from the some Turkish sheep breeds. Haematological parameters of crossbreed sheep were most likely similar to Sakız sheep from which 75% of genotype of crossbreed sheep were earn.